Can radiological changes in lymph node volume during treatment predict success of radiation therapy in patients with locally advanced head and neck squamous cell carcinoma?. Issue 5 (8th May 2013) - Mishra, Sanju; Hammond, Alexander; Read, Nancy; Venkatesan, Varagur; Winquist, Eric; Nichols, Anthony; Warner, Andrew; Palma, David
Abstract Background Assessment of nodal response after radiotherapy (RT) for head and neck squamous cell carcinoma is difficult, as both CT and positron emission tomography scanning have limited predictive value for residual disease. We sought to measure changes in nodal volume during RT to determine whether such changes are predictive of nodal disease control. Methods Patients with locally advanced head and neck squamous cell carcinoma treated with 70 Gy of radical RT (±chemotherapy or anti‐epidermal growth factor receptor (EGFR) antibodies) were eligible. Baseline pre‐RT scans and cone‐beam CT scans done at the outset of treatment and at weeks 3, 5 and 7 (cone‐beam CTs # 1, 2, 3 and 4, respectively) were deformably coregistered, and 3D nodal volumes were measured. Results Thirty‐eight eligible patients were identified. The main primary tumour site was oropharyngeal; most patients had stage IVa disease. Twenty‐seven patients received concurrent platinum‐based chemotherapy, 10 received only an EGFR inhibitor with RT and one received RT alone. Twelve patients had a failure in the neck. After week 1 of treatment, a 4% mean decrease in nodal volume was observed, increasing to 40% at week 7. Platinum‐based chemotherapy achieved significantly greater decreases in nodal volume than EGFR inhibitors (44 vs. 25%; P = 0.026). Advanced tumour stage predicted neck failure (P = 0.002), but nodal volumes did not correlate with neck control. Conclusions Changes in nodal volume are minimal initially during RT but accelerate during the latter weeks of therapy. This study suggests that chemotherapy achieves a greater decrease in nodal volume than EGFR inhibitors and that nodal changes do not predict disease control in the neck.